COMMUNITY SECURITY AND ORDERS MANAGEMENT BY VILLAGE GOVERNMENT AND BHABINKAMTIBMAS - Rudiana, Rudiana; Dharmawan, Ivan; Nugraha, Ginanjar Diki (Department of Government, FISIP, Universitas Padjadjaran, 2021)
Security and order were social life's needs and would create a comfortable and harmonious environment. That condition would carry out their daily lives, which will implicate their community welfare. The government as an organizer and community were responsible for security and order. The public was demanded to be aware and participate in creating security and order. The Head of the village was responsible for coordination with 'Bhayangkara Pembina Keamanan dan Ketertiban Masyarakat' – known as Bhabinkamtibmas – to make the environment's security and order within the village government. This study used the descriptive qualitative method which provides an overview of coordination between the village government and Bhabinkamtibmas. Primary and secondary data were used which were obtained through observation, interviews, literature study, and documentation. The purposive technique was used to determine the informants of data information. Village government and Bhabinkamtibmas coordination about security and order were explained in the study's results, viewed by seven indicators: Information, Communication and Technology, Importance of Coordination Awareness, Participant Competence, Agreement and Commitment, Establishment of Agreements, Coordination Incentives, and Feedback.